2007
DOI: 10.1007/s00586-007-0546-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of shoulder balance in the normal adolescent population and its correlation with radiological parameters

Abstract: A descriptive clinical study in healthy adolescents was done to evaluate the clinical shoulder balance and analyze the correlation between clinical and radiological parameters which are currently used to evaluate shoulder balance. In addition to trunk shift and rib hump, shoulder balance is one of the criteria that are used to evaluate the outcomes in spinal deformity surgery. Several methods have been proposed to evaluate the shoulder balance in scoliotic patients; however, there is no uniformity to these met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 4 publications
5
84
0
7
Order By: Relevance
“…It is the method of choice for assessing radiological shoulder balance; differences of more than 9 mm correlate with shoulder imbalances of [10 mm [7]. In our study, all of the patients had preoperative a CHD of [9 mm; postoperatively there was significant improvement in CHD, but most of the patients still had CHD [9 mm.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It is the method of choice for assessing radiological shoulder balance; differences of more than 9 mm correlate with shoulder imbalances of [10 mm [7]. In our study, all of the patients had preoperative a CHD of [9 mm; postoperatively there was significant improvement in CHD, but most of the patients still had CHD [9 mm.…”
Section: Discussionmentioning
confidence: 49%
“…It has the additional advantage of being the method of choice when the shoulders are not included in the X-ray [7]. CTAD [ 4.5°i ndicates a clinical shoulder imbalance of [10 mm [7].…”
Section: Discussionmentioning
confidence: 99%
“…Clavicle-rib cage intersection difference (CRID) is known as the distance between the horizontal lines drawn through the intersecting points of the superior aspects of each clavicle with the outer edge of the second rib's insertio ( Figure 4) [3][4][5]. The clavicular tilt angle difference (CTAD) is the difference between the angles formed by the bisection of the lines of the proximal portions of the clavicle with the horizontal (Figure 4) [4].…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this retrospective study was to evaluate the effects of the three distinct growth guidance techniques on shoulder balance in the coronal-plane, by measuring the following radiographical parameters of shoulder balance (difference of coracoid process height-CHD, clavicula-tilt angle-CTAD and clavicula-rib cage intersection point-CRID) [3][4][5] that were obtained in the preoperative, postoperative and final follow-up period which underwent statistical analysis in comparison with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [5,6] have shown that there is weak correlation between radiographic parameters and posterior clinical shoulder balance (Sh.B), and the principles of deformity correction involve consideration of not only the correction of radiographic measures but also that of clinical appearance. As an example, correction of only radiographic parameters in Lenke 2 curves may lead to a decompensated shoulder imbalance if the clinical appearance is not considered in surgical planning [7][8][9].…”
Section: Introductionmentioning
confidence: 99%